An Investigation into Researchers’ Awareness and Consideration of Ethical Issues in Social Science Research: A Survey of Selected Research Centres of the Ministry of Scientific Research and Innovation, Yaounde, Cameroon - Arrey-Ndip, Nkongho A. (Journal of Humanities and Social Sciences Studies, 2020)
This study investigates researchers’ awareness and consideration of ethical issues in social research. The study focuses on a broad range of ethical issues that would normally be taken into consideration in the course of doing social research. The main focus in this study was to place emphasis on the notion that social researchers ought to be aware of the ethical issues that make up their practice, and be in a position to be able to apply or consider these principles in the course of their work. This study is a mixed method research design employing both quantitative survey with some open-ended questions. The population for the study was made up of all the 140 researchers in the two research structures or centres involved in this study. Fifty questionnaires were administered and 46 were completed and returned, representing a 92 percent return rate. The results of this study show that participants were generally aware of ethical issues in social research, albeit to varying degrees. In spite of this awareness, it would seem, in most cases, there was no strong indication that participants were likely to consider/ have considered same in their work. It was partly concluded that to enhance the awareness and consideration of ethical issues of the researchers in the centres involved in this study would require an attitudinal shift concerning the positive contributions and the benefits that research ethics could make to social science research –a shift which could bring a significant change in ethical practices in the centres; and lead to the possibility of developing in-house ethical statements or principles to guide researchers in their work.